Compliant actuation based on dielectric elastomers for a force-feedback device: modeling and experimental evaluation - R. Vertechy; M. Bergamasco; G. Berselli; V. Parenti Castelli; G. Vassura (Fracture and Structural Integrity)
Thanks to their large power densities, low costs and shock-insensitivity, Dielectric Elastomers (DE) seem to be a promising technology for the implementation of light and compact force-feedback devices such as, for instance, haptic interfaces. Nonetheless, the development of these kinds of DE-based systems is not trivial owing to the relevant dissipative phenomena that affect the DE when subjected to rapidly changing deformations. In this context, the present paper addresses the development of a force feedback controller for an agonist-antagonist linear actuator composed of a couple of conically-shaped DE films and a compliant mechanism behaving as a negative-rate bias spring. The actuator is firstly modeled accounting for the visco-hyperelastic nature of the DE material. The model is then linearized and employed for the design of a force controller. The controller employs a position sensor, which determines the actuator configuration, and a force sensor, which measures the interaction force that the actuator exchanges with the environment. In addition, an optimum full-state observer is also implemented, which enables both accurate estimation of the time-dependent behavior of the elastomeric material and adequate suppression of the sensor measurement noise. Preliminary experimental results are provided to validate the proposed actuator-controller architecture.